Muslim Father's Rights in Determining His Minor Child's Conversion to Islam in Malaysia - Kusrin, Zuliza Mohd; Hamjah, Salasiah Hanin; Sham, Fariza Md (European Journal of Social Science Education and Research, 2022)
Freedom of religion is guaranteed by the Federal Constitution of Malaysia. For children, their rights to freedom of religion are mentioned in Article 12(4) of the Federal Constitution. However, there is conflict of law, i.e. between the civil law and Sharia Law, in some cases involving the child's conversion to Islam, following the conversion of his or her parents. This article aims to discuss on provisions of the Federal Constitution on the child's right to the freedom of religion. The discussion also elucidate on the father's right in determining his minor child's conversion to Islam. The methodology used in gathering relevant data is content analysis. Data was gathered from Sharia Laws, legal provisions, law journals and reported cases relevant to the issue. The data has been analyzed descriptively. The discussion discovered that civil court has competent jurisdiction in hearing cases that involves issues of conversion of children following the conversion of only his/her father or mother. In earlier cases of conversion to Islam, it was decided that the minor child's religion is following the religion of his or her converted father/mother. However, in the later cases the court has decided that the religion of the children is remain as the religion of their parents, before the conversion to Islam.
Keywords: religion, minor, father, conversion, Islam